ADOPSI METODE ACTION RESEARCH UNTUK MENINGKATKAN KINERJA INTERNET NETWORK DI PROV. SUMSEL - Bitrayoga, Muhammad; Antoni, Darius; Herdiansyah, M Izman; Syamsuar, Dedy (Universitas Lembah Dempo, 2021)
A computer network is a group of computers that are connected to one another by using a communication protocol through transmission media or communication media so that they can share data, programs, share hardware such as printers, hard drives and so on. The purpose of the measurement is to obtain measurement results on Virtual Private Network (VPN) network technology with parameters of Throughput (KBps), Delay (ms) and Packet loss (%), in order to analyze the results of QoS (Quality Of Service) performance of Virtual Private Network networks. (VPN) servers that meet the standards of good service quality and efficiency. The method used is Action Research which is an action research aimed at developing the most efficient work method. With action research. Action research is divided into several stages which are cycles, namely: Performing diagnostics (diagnosing), Making an action plan (action planning), Taking action (action taking), Conducting evaluation (evaluating), and Learning (learning) and measurement results of delay parameters and packet loss greatly affects the value of throughput where the greater the value of delay and packet loss, the smaller the resulting throughput value. The value of delay and packet loss is getting smaller, the better, while the bigger the worse, while the throughput parameter is on the contrary, where the bigger the better, the thing that greatly affects the value of the measurement of delay, packet loss and throughput on VPN networks besides attenuation and noise is the amount of bandwidth given so that it is very important. affect the measurement of the QoS value as for the suggestions to be conveyed in this study is to increase the bandwidth on the VPN network so that it has very small delay and packet loss values ??and large throughput so that a better QoS value can be obtained.